Time-driven effects on processing grammatical agreement - Roll, Mikael; Gosselke, Sabine; Lindgren, Magnus; Horne, Merle (Frontiers in Psychology, 2013)
‘Agreement’ is a grammatical relation between words; e.g., the verbal suffix –s reflects agreement with a singular subject (He run-s). Previous studies with time intervals under 2.5 s between disagreeing words have found a left-lateralized negative brain potential, arguably reflecting detection of the morphosyntactic violation. We tested the neurophysiological effects of number agreement between the first and last word in sentences at temporal distances between 1.75 and 3.25 s. Distances were varied by visually presenting sentences word by word at different rates. For distances under 2.5 s, a left-lateralized negativity was observed. At a 3.25-s interval, an anterior, slightly right-lateralized negativity was found. At an intermediate distance of 2.75 s, the difference between disagreement and agreement at left electrodes correlated with participants’ working memory span. Results indicate that different brain processes occur when agreement involves agreement domains approaching and exceeding 3 s than when the agreement dependency involves shorter temporal intervals.